PERAN KEPENGURUSAN IPNU DAN IPPNU DALAM MENJAGA TATA TERTIB DI MADRASAH ALIYAH FATHUL HIDAYAH PANGEAN MADURAN LAMONGAN - Ahmad Ishom Tamimi; Nur Hasan; Syamsu Madyan (VICRATINA, 2022)
This study discusses the role of IPNU and IPPNU management in maintaining order at Madrasah Aliyah Fathul Hidayah Pangean Maduran Lamongan. This research is motivated by why IPNU-IPPPNU student organizations can interfere in maintaining order at MA Fathul Hidayah. The method used in this research is a type of qualitative research with a case study method with interview, observation, and documentation techniques, then researchers get the information needed. After finding the results, the researcher analyzed the data by means of data collection, data reduction and data verification. The results of this study indicate that the IPNU-IPPNU student organization has a strategic position, namely as an intra-school organization, the efforts made to maintain order are in charge of maintaining order and student discipline, and the obstacles faced are when facing their own friends, less consistent in their work. duty, and lack of coordination.